Keepers of the earth : native American stories and environmental activities for children - Caduto, Michael J.; Bruchac, Joseph, 1942-; Ka-Hon-Hes; Wood, Carol (Golden, Colo. : Fulcrum, 1988)
A selection of traditional tales from various Indian peoples, each accompanied by instructions for related activities dealing with aspects of the environment.
The Coming of Gluscabi (Abenaki -- Northeast Woodlands) -- The Earth on turtle's back (Onondaga -- Northeast Woodlands) -- Four worlds: The Dine story of creation (Dine / Navajo -- Southwest) -- Loo-Wit, the fire-keeper (Nisqually -- Pacific Northwest) -- How Grandmother Spider stole the sun (Muskogee / Creek -- Oklahoma) -- Tunka-shila, grandfather rock (Lakota / Sioux -- Great Plains) -- Old man coyote and the rock (Pawnee -- Great Plains) -- Gluscabi and the wind eagle (Abenaki -- Northeast Woodlands) -- The Hero twins and the swallower of clouds (Zuni -- Southwest) -- How thunder and earthquake made ocean (Yurok -- California) -- Sedna, the woman under the sea (Inui -- Arctic Regions) -- How raven made the tides (Tsimshian -- Pacific Northwest) -- How coyote was the moon (Kalispel -- Idaho) -- How fisher went to the skyland: The Origin of the Big Dipper (Anishinabe -- Great Lakes Region) -- Spring defeats winter (Seneca -- Northeast Woodlands) -- The Coming of corn (Cherokee -- North Carolina) -- Manabozho and the maple trees (Anishinabe -- Great Lakes Region) -- Kokopilau, the hump-backed flute player (Hopi -- Southwest) -- How turtle flew south for the winter (Dakota / Sioux -- Midwest) -- Gluscabi and the game animals (Abenaki -- Northeast Woodlands) -- Awi Usdi, the little deer (Cherokee -- North Carolina) -- The Origin of death (Siksika / Blackfeet -- Montana) -- The White Buffalo Calf Woman and the sacred pipe (Lakota / Sioux -- Great Plains) -- Koluscap and the water monster (MicMac and Maliseet -- Nova Scotia)
Includes index.
Keywords: Indians of North America -- Folklore; Indian mythology -- North America; Nature craft -- Juvenile literature